Landscape Design of Mutiara Garden Housing Park as a Source of Infiltration in Residential Areas - Morian Saspriatnadi; Gun Faisal; Indra Kuswoyo (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Green Open Space (RTH) plays an important role in the ecosystem and balance for both living things and the surrounding environment. The condition of the planning site that extends north to south is in the middle of a housing complex. The planned facilities include a playground, watersplash plaza, children's pool, seating corner, gazebo, community garden, tropical pocket park and tropical striping park, veranda walkway. With the concept of "Tropical Community Escape" certainly helps strengthen the function of the design as an area that accommodates recreational, sports, social and cultural activities. From the design that has been made in general it has filled about 60% more of the area that can absorb water with the selection of the right material and reducing water-resistant materials and the use of trees and shrubs in the design which can fulfill as catchment areas.